Effect of Aqueous Leaves Extract of Balanite Aegyptiaca on Some Biochemical and Haematological Parameters in Wistar Rats - Isah, S.Y. *, Ahmad, I. M., Hamid, K. M., Abdulhadi, A.U., Abdullahi, H.L, Danladi, S.B., Ahmad, M. B., Rogo, L.D. (Sokoto Journal of Medical Laboratory Science)
There is exponential interest in phytotherapy and the demands for information on the effect and implications of the various plant material used in the management of diseases because it is scanty particularly in most developing countries. This study is aimed at determining the effect of aqueous leaves extract of Balanite aegyptiaca on some biochemical and haematological parameters in Wistar rats. A total of twenty-eight (28) Wistar rats were used in the study (twelve was use for acute toxicity studies, with very high concentrations of Aqueous extract of Balanite aegyptiaca no mortality was recorded). Sixteen (16) Wistar rats were divided into four (4) groups. Group I served as control, group II to IV were administered orally with 300, 400 and 500mg/kg aqueous leaves extract of Balanite aegyptiaca daily for 21days. Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Alkaline phosphatase (ALP), total bilirubin (TB), direct bilirubin (DB), albumin, total protein, electrolytes (K+, Na+, Cl-, Ca2+), urea, creatinine and some haematological parameters (WBC, RBC, HCT, MCV, MCH, MCHC), were analysed using standard laboratory Techniques. The results of the acute toxicity studies indicate that this extract is well tolerated at doses as high as 5000mg/kg body weight. The result of the study showed that, the total protein, creatinine, haematocrit and haemoglobin showed a significant increase (p<0.05) with increased dose when compared with the control. However, no significant differences in other parameters (p>0.05) was observed when compared with the control. Based on the result of this study, it may be considered that aqueous leaves extract of Balanites aegyptiaca administered for up to 21 days may not be hepatotoxic, does not alter electrolyte and some haematological parameters. Its ability to increase erythrocyte may make it useful in management of mild anaemia. Aqueous leaves extract may be nephrotoxic with increased creatinine levels following an increase in the dose and prolong usage.